2008
DOI: 10.1128/jvi.01215-08
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Protein pp71 Displaces the Chromatin-Associated Factor ATRX from Nuclear Domain 10 at Early Stages of Infection

Abstract: The human cytomegalovirus (HCMV) tegument protein pp71, encoded by gene UL82, stimulates viral immediate-early (IE) transcription. pp71 interacts with the cellular protein hDaxx at nuclear domain 10 (ND10) sites, resulting in the reversal of hDaxx-mediated repression of viral transcription. We demonstrate that pp71 displaces an hDaxx-binding protein, ATRX, from ND10 prior to any detectable effects on hDaxx itself and that this event contributes to the role of pp71 in alleviating repression. Introduction of pp7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(154 citation statements)
references
References 62 publications
5
148
1
Order By: Relevance
“…There is increasing evidence that several ND10 components contribute to intrinsic cellular resistance to a variety of herpesvirus infections (Cantrell and Bresnahan, 2006;Everett et al, 2008a;Kyratsous and Silverstein, 2009;Ling et al, 2008;Lukashchuk et al, 2008;Lukashchuk et al, 2010;Negorev et al, 2006;Preston and Nicholl, 2006;Saffert and Kalejta, 2006;Tavalai et al, 2006;Tavalai et al, 2008;Woodhall et al, 2006). We have shown that depletion of PML increases the replication efficiency of ICP0-null mutant HSV-1 (Everett et al, 2008a;Everett et al, 2006;Everett et al, 2008b), a finding that implicates PML in a repression mechanism that targets HSV-1 genomes and which is inactivated by ICP0 during the course of a wild-type virus infection.…”
Section: Discussionmentioning
confidence: 76%
“…There is increasing evidence that several ND10 components contribute to intrinsic cellular resistance to a variety of herpesvirus infections (Cantrell and Bresnahan, 2006;Everett et al, 2008a;Kyratsous and Silverstein, 2009;Ling et al, 2008;Lukashchuk et al, 2008;Lukashchuk et al, 2010;Negorev et al, 2006;Preston and Nicholl, 2006;Saffert and Kalejta, 2006;Tavalai et al, 2006;Tavalai et al, 2008;Woodhall et al, 2006). We have shown that depletion of PML increases the replication efficiency of ICP0-null mutant HSV-1 (Everett et al, 2008a;Everett et al, 2006;Everett et al, 2008b), a finding that implicates PML in a repression mechanism that targets HSV-1 genomes and which is inactivated by ICP0 during the course of a wild-type virus infection.…”
Section: Discussionmentioning
confidence: 76%
“…The homologous ATRX remodeler contains an ADD (ATRX-DNMT3-DNMT3L) domain that can bind DNA or histone tails (16)(17)(18). Indeed, ATRX is recruited to the genomes of DNA viruses as they enter the nucleus, suggesting that it may directly bind exposed DNA (19). A recent study has shown that the mammalian Hira chaperone may also directly bind exposed DNA at chromatin gaps (20).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well-known that pp71 degrades a chromatin-remodeling factor, hDaxx, followed by disruption of the hDaxx-ATRX complex (36,37) and members of the retinoblastoma tumor-suppressor family of proteins (38). The disruption of the hDaxx-ATRX complex can cause genomic instability (39) whereas the loss of retinoblastoma family proteins dysregulates normal cell-cycle progression (40,41).…”
Section: Discussionmentioning
confidence: 99%